In Vivo Imaging of Retinoic Acid Receptor Activity using a Sodium/Iodide Symporter and Luciferase Dual Imaging Reporter Gene - Min Kyung So; Joo Hyun Kang; June-Key Chung; Yong Jin Lee; Jae Hoon Shin; Kwang Il Kim; Jae Min Jeong; Dong Soo Lee; Myung Chul Lee (Molecular Imaging, 2004)
Retinoic acids are natural derivatives of vitamin A, and play important roles in modulating tumor cell growth by regulating differentiation, thus suggesting the potential use of these derivatives in cancer therapy and prevention. To visualize the intranuclear responses of functional retinoic acid receptors, we have developed a dual-imaging reporter gene system based on the use of sodium/iodide symporter (NIS) and luciferase in cancer cell lines. NIS and luciferase genes were linked with an internal ribosome entry site, and placed under the control of an artificial cis -acting retinoic acid responsive element (pRARE/NL). After retinoic acid treatment, I-125 uptake by pRARE/NL transfected cells was found to have increased by up to about five times that of nontreated cells. The bioluminescence intensity of pRARE/NL transfected cells showed dose-dependency. In vivo luciferase images showed higher intensity in retinoic acid treated SK-RARE/NL tumors, and scintigraphic images of SK-RARE/NL tumors showed increased Tc-99m uptake after retinoic acid treatment. The NIS/luciferase imaging reporter system was sufficiently sensitive to allow the visualization of intranuclear retinoic acid receptor activity. This cis -enhancer imaging reporter system may be useful in vitro and in vivo for the evaluation of retinoic acid responses in such areas as cellular differentiation and chemoprevention.